Effects of different sources of selenium supplementation on antioxidant indices, biochemical parameters, thyroid hormones and Se status in transition cows (Acta Scientiarum. Animal Sciences, 2019)
The aim of this study was to determine the effects of supplementing close-up and fresh dairy cows’ diets with sodium selenite or organic sources of selenium (Se) on the serum biochemical parameters and antioxidant indicators and Se status. Twenty-four multiparous Holstein dairy cows were balanced by body condition score (BCS), previous lactation milk yield and expected calving date and randomly assigned to 1 of 4 experimental treatments. Treatments were: control (basal diet without Se supplementation), sodium selenite supplementation (0.50 mg of Se kg-1 DM; Se-S), selenium yeast supplementation (0.50 mg of Se kg-1 DM; Se-Y) and selenomethionine supplementation (0.50 mg of Se kg-1 DM; Se-M). Serum Se concentrations were higher for cows in Se-Y (72.34 µg dL-1) and Se-Met (72.34 µg dL-1) than control (59.93µg/dl) and Se-S (64.79µg/dl). The Se supplementation and sources did not affect serum metabolites or indices of antioxidant pre and postpartum, except serum total protein and albumin concentrations. Cows in Se-M had greater serum total protein and albumin concentrations than those in control. The results of present study showed that serum Se concentrations increased in Se-Y and Se–M more effectively than Se-S, indicating that selenomethionine could replace Se-S as an effective organic Se source for transition dairy cows.